A review of the recent progress of stand-alone photovoltaic-battery hybrid energy systems in space and on the ground. (25th November 2022) - Xie, Jingyan; Li, Yun-Ze; Yang, Lizhu; Sun, Yuehang; Yuan, Man
Abstract: The stand-alone photovoltaic-battery (PV/B) hybrid energy system has been widely used in off-grid equipment and spacecraft due to its effective utilization of renewable energy. For they are interconnected and distinct from each other, the ground and space stand-alone PV/B hybrid energy systems are compared in this review. On the one hand, advanced and well-established technologies are demanded in both fields. On the other hand, special needs are also demonstrated due to the different working environments and tasks. A considerable amount of academic research has accumulated on the ground and space stand-alone PV/B hybrid energy systems. Nevertheless, the existing research directions are quite disorganized and unbalanced for both space and ground stand-alone PV/B hybrid energy systems. For this reason, there is a strong drive to collect recent research and conduct a clear, balanced literature review. In the first place, dilemmas of the stand-alone PV/B hybrid energy system in different scenarios were analyzed. Then, the current system-level solutions were summarized. Moreover, the development history and new research results on the component level of solar cells and secondary batteries were introduced. The progress of lithium battery performance in a low-temperature environment was highlighted. Finally, the study pointed out possible development directions of the stand-alone PV/B hybrid energy system in space and on the ground. The primary contributions of this review are: (i) a detailed contrastive analysis of the working characteristics and difficulties of the stand-alone PV/B hybrid energy system in space and on the ground, (ii) a comprehensive review of the literature that summarize past and current design trends by synthesizing the different sources of information. This article could provide new insights and possible future research directions for the professionals. Highlights: Focusing on the stand-alone PV/B hybrid energy system in space and on the ground. The challenges faced by the system in both conditions are mentioned and compared. Technical development in system-leve and component-level are provided. Recent results about overcoming extreme temperatures are highlighted.